2018
DOI: 10.1101/331322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GoFish: A Streamlined Environmental DNA Presence/Absence Assay for Marine Vertebrates

Abstract: 21Here we describe GoFish, a streamlined environmental DNA (eDNA) presence/absence 22 assay. The assay amplifies a 12S segment with broad-range vertebrate primers, followed by 23 nested PCR with M13-tailed, species-specific primers. Sanger sequencing confirms positives 24 detected by gel electrophoresis. We first obtained 12S sequences from 77 fish specimens 25 representing 36 northwestern Atlantic taxa not well documented in GenBank. Using the newly 26 obtained and published 12S records, we designed GoFish as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Ship-and shore-based manual sampling methods constrain most field sampling to weekly visitations at best (Bista et al, 2017;Sigsgaard et al, 2017;Stoeckle et al, 2017Stoeckle et al, , 2018. To our knowledge, only a few studies have reported hourly or highfrequency sampling over short durations to investigate the effects tides (Kelly et al, 2018) or spawning events (Tillotson et al, 2018) have on eDNA signals.…”
Section: Autonomous Mobile Sampling Systems For Ednamentioning
confidence: 99%
“…Ship-and shore-based manual sampling methods constrain most field sampling to weekly visitations at best (Bista et al, 2017;Sigsgaard et al, 2017;Stoeckle et al, 2017Stoeckle et al, , 2018. To our knowledge, only a few studies have reported hourly or highfrequency sampling over short durations to investigate the effects tides (Kelly et al, 2018) or spawning events (Tillotson et al, 2018) have on eDNA signals.…”
Section: Autonomous Mobile Sampling Systems For Ednamentioning
confidence: 99%
“…To apply several species delimitation methods to infer MOTUs, our samples were combined with COI sequences from 19 Squatina nominal species (Table 2, Table S1) obtained from the public repository BOLD (www.boldsystems.org, accessed on 5 February 2021), GenBank (www.ncbi.nlm.nih.gov/genbank/, accessed on 5 February 2021), and from the literature [5,35,36,43,[47][48][49][50][51][52][53][54][55][56]. The set of DNA fragments were chosen following two criteria: (1) the location of sampling mentioned in the public database (e.g., country, province, region, sector, exact site, coordinates or FAO fishing zones) and ( 2) length of the DNA fragment (i.e.,~610 bp).…”
Section: Species Delimitation Methodsmentioning
confidence: 99%